2013
DOI: 10.1111/sjoe.12038
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Credit Growth and International Capital Flows*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
168
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(190 citation statements)
references
References 58 publications
13
168
1
3
Order By: Relevance
“…Our results is consistent with several studies, such as those of Caballero (2014) and Lane and McQuade (2014), that have shown that debt inflows are linked to the growth of domestic credit, and often more bank crises.…”
Section: Resultssupporting
confidence: 82%
“…Our results is consistent with several studies, such as those of Caballero (2014) and Lane and McQuade (2014), that have shown that debt inflows are linked to the growth of domestic credit, and often more bank crises.…”
Section: Resultssupporting
confidence: 82%
“…For a sample of European countries, Lane and McQuade (2012) find that international capital inflows were indeed correlated with domestic credit growth during the 2003-2008 pre-crisis period. In particular, a high level of net debt inflows was associated with more rapid domestic credit growth, as is shown in Figure ??.…”
Section: Financial Globalisation and Sources Of The Crisismentioning
confidence: 99%
“…In other words, the adverse effects of public debt on private credit growth might be reduced if countries can raise funds abroad (see Lane and McQuade 2013 for an application to European countries for the 2003-08 boom period).…”
Section: Controlling For the Ability To Access Foreign Resourcesmentioning
confidence: 99%